Analisis Perputaran Persediaan dan Penjualan Terhadap Laba Bersih Pada PT Tunas Baru Lampung Tbk - Saridawati; Kuswardani, Avrilla; Handayani, Nita Tri; Azizah, Zahra Nur (Cattleya Darmaya Fortuna, 2024)
Inventory turnover ratio has an important role for companies. Inventory turnover ratio is used to assess the efficiency of companies that can sell and replace inventory at a period. Inventory turnover ratio is needed to improve operational efficiency and corporate profitability. A high inventory turnover ratio indicates that the company is selling supplies quickly and inventory management is doing well. Meanwhile, if the inventory turnover ratio is low, it shows that the supply is not sold quickly, resulting in inventory buildup and high storage costs. This certainly affects the company's sales and profits. This study analyzed the effect of inventory turnover and sales on net profit in PT Tunas Baru Lampung Tbk from 2019 to 2023. The purpose of research on inventory turnover and sales analysis on net profit at PT Tunas Baru Lampung Tbk is to find out the effect of inventory turnover and sales on the company's net profit. This study analyzed the company's sales and profitability. This analysis study used a quantitative method by approaching financial ratios in the form of activity ratios. The data analyzed is the Annual Financial Report of PT Tunas Baru Lampung Tbk covering the Profit and Loss Report and the Financial Position Report from 2019 to 2023. The results of research on inventory turnover and sales analysis on net profit at PT Tunas Baru Lampung Tbk show that inventory turnover regarding the company's inventory management has an effect on sales. And the turnover of inventory against profit also affects the company's net profit. The increase in inventory turnover and the turnover of inventory to profit is in line with the increase in sales and net profit of the company. On the other hand, if the inventory turnover and inventory turnover against profit decrease, the company's sales and net profit also decrease.